(untitled) (Altre Modernità, 2017)
This study deals with the implementation of a renewed globalized and integrating passion on the part of the South American Church with its new pontificate, from a semiotic-cultural point of view. This can be drawn from Pope Francis’s words in recent apostolic visits to different Latin countries: Cuba, Bolivia and Paraguay (2015-2016). The rhetorical and passionate strategies of this pontificate in South America aim to change the (com-passionate and counter-passionate) modal competences of the social players involved, depending on the linguistic, metaphoric-experiential, and cultural heritage of each country convened.